Metformin in polycystic ovary syndrome: unraveling multi-stage therapeutic mechanisms from puberty to long-term health outcomes - Zeng, Weiwei; Luo, Yuning; Ou, Juanfeng; Gan, Dali; Huang, Min; Tomlinson, Brian; Jiang, Yiming (Frontiers in Pharmacology, 2025)
Polycystic ovary syndrome (PCOS) represents a prevalent endocrine disorder affecting reproductive-aged women worldwide, characterized by a variety of reproductive, metabolic, and psychological manifestations. This condition disrupts menstrual cycles and fertility, and significantly compromises quality of life, while increasing the risk of severe health consequences, including cardiovascular diseases and endometrial carcinoma. Although the precise etiology of PCOS remains elusive, genetic and environmental factors are thought to contribute to its pathogenesis. In recent years, the escalating global prevalence of PCOS has been observed, and pharmacological intervention has become the primary treatment approach. Metformin, an insulin sensitizer, has emerged as a valuable treatment option in PCOS management. Multiple studies have suggested that metformin have a positive impact on puberty problems, pregnancy complications, and long-term health outcomes in women with PCOS. However, persistent controversies surround its therapeutic efficacy and underlying molecular mechanisms. This review systematically examines the mechanisms of metformin in ameliorating PCOS-associated infertility, with particular emphasis on its pleiotropic effects across critical life stages—from pubertal development through pregnancy to long-term health outcomes, thereby providing valuable insights into the clinical application of metformin in the treatment of PCOS.